2011
DOI: 10.1177/1934578x1100600832
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial activity of Satureja kitaibelii Essential Oil against Pathogenic Microbial Strains

Abstract: Plant species Satureja kitaibelii Wierzb. ex Heuff. is used as a spice and as a natural preservative for food and herbal tea, owing to its characteristic scent and flavor as well as high antimicrobial activity. In the present study, the antimicrobial activity of isolated essential oil of S. kitaibelii was tested against a panel of 30 pathogenic microorganisms (foodborne microbes, selected multiresistant bacterial isolates from the patient wounds and dermatophyte isolates). Limonene (15.54%), p-cymene (9.99%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
4
13
0
Order By: Relevance
“…Beside the most commonly used species S. hortensis and S. montana, the herb of S. kitaibelii, endemic of Balkan Peninsula, [6] is also frequently used and commercially available under the name of "Rtanj tea" and it is used in traditional medicine for ages to treat diarrhea, nausea, cramps, muscle pain, indigestion, fertility, menstrual disorders, respiratory and infectious diseases, in aromatherapy, and in mediterranean kitchen as a culinary herb. [8][9][10][11] The essential oil composition of S. kitaibelii species is very variable. According to some authors, dominant components in the essential oil of this species is p-cymene [11−14] while Miladinović [15] reported geraniol as the main one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside the most commonly used species S. hortensis and S. montana, the herb of S. kitaibelii, endemic of Balkan Peninsula, [6] is also frequently used and commercially available under the name of "Rtanj tea" and it is used in traditional medicine for ages to treat diarrhea, nausea, cramps, muscle pain, indigestion, fertility, menstrual disorders, respiratory and infectious diseases, in aromatherapy, and in mediterranean kitchen as a culinary herb. [8][9][10][11] The essential oil composition of S. kitaibelii species is very variable. According to some authors, dominant components in the essential oil of this species is p-cymene [11−14] while Miladinović [15] reported geraniol as the main one.…”
Section: Introductionmentioning
confidence: 99%
“…Chalchat et al [12] identified 33 compounds in S. kitaibelii essential oil (population from the site Rtanj, eastern Serbia) with main ones being p-cymene (33.6%), carvacrol (14.1%), limonene (8.4%), and cis-sabinene hydrate (5.5%). Besides them, Slavkovska et al, [13] Mihajilov-Krstev et al, [11] and Kundaković et al [14] declared p-cymene as dominant or one of the most dominant compound in their samples of S. kitaibelii essential oil. It is notable that these samples (reported by authors mentioned above) varied significantly from the ones processed in this study regarding the major compound.…”
mentioning
confidence: 96%
“…Almost all of methanol extracts exhibit moderate antimicrobial activity. A. alpinus extract displayed slightly more pronounced antimicrobial activity, which can be attributed to the presence of thymol as the major component [22][23][24][25]. Significant antimicrobial activity of phenolic derivatives, especially thymol and carvacrol, as well as their biosynthetic precursors γ-terpinene and p-cymene, was confirmed [26].…”
mentioning
confidence: 99%
“…Recently, many studies have focused on the antimicrobial activity of the essential oil and extracts of Satureja species. These studies have revealed that the genus has antimicrobial activity against human, food and plant pathogens [20][21][22] due to the presence of phenolic components, such as thymol and carvacrol. A large number of studies have reported that the essential oils of Satureja species are among the most potent essential oils regarding their antimicrobial properties [23][24][25].…”
mentioning
confidence: 99%